Review Of Psychological Adaptation Factors of International Students in Russian Universities Of the Russian Federation - Alisher Komiljonovich Sanayev; Pavel Nikolayevich Ustin; Murotmusaev Komiljon Buribaevich (Genius Journals, 2022)
This article reviews and analyzes the process of adaptation of foreign students who have arrived to study in Russian universities. The absolute majority of foreign citizens upon arrival to Russia encounter many difficulties of both physiological and of socialpsychological character. The article presents the options, which are considered by the researchers to be the key ones in the process of of adaptation of foreign students to the conditions of the university.
Keywords: International students; adaptation; factors adaptation.